A Novel Antimicrobial Endolysin, LysPA26, against Pseudomonas aeruginosa - Guo, Mingquan; Feng, Chunyan; Ren, Jie; Zhuang, Xuran; Zhang, Yan; Zhu, Yongzhang; Dong, Ke; He, Ping; Guo, Xiaokui; Qin, Jinhong (Frontiers in Microbiology, 2017)
The global increase in multidrug-resistant (MDR) bacteria has led to phage therapy being refocused upon. A novel endolysin, LysPA26, containing a lysozyme-like domain, was screened against Pseudomonas aeruginosa in this study. It had activity against MDR P. aeruginosa without pretreatment with an outer-membrane permeabilizer. LysPA26 could kill up to 4 log units P. aeruginosa in 30 min. In addition, temperature and pH effect assays revealed that LysPA26 had good stability over a broad range of pH and temperatures. Moreover, LysPA26 could kill other Gram-negative bacteria, such as Klebsiella pneumonia, Acinetobacter baumannii and Escherichia coli, but not Gram-positive bacteria. Furthermore, LysPA26 could eliminate P. aeruginosa in biofilm formation. Our current results show that LysPA26 is a new and promising antimicrobial agent for the combat of Gram-negative pathogens.